Molecular Signatures of a TLR4 Agonist-Adjuvanted HIV-1 Vaccine Candidate in Humans - Anderson, Jenna; Olafsdottir, Thorunn A.; Kratochvil, Sven; McKay, Paul F.; Östensson, Malin; Persson, Josefine; Shattock, Robin J.; Harandi, Ali M. (Frontiers in Immunology, 2018)
Systems biology approaches have recently provided new insights into the mechanisms of action of human vaccines and adjuvants. Here, we investigated early transcriptional signatures induced in whole blood of healthy subjects following vaccination with a recombinant HIV-1 envelope glycoprotein subunit CN54-gp140 adjuvanted with the TLR-4 agonist glucopyranosyl lipid adjuvant–aqueous formulation (GLA-AF) and correlated signatures to CN54-gp140 specific serum antibody responses. Fourteen healthy volunteers aged 18-45 years were immunized intramuscularly three times at one-month intervals and whole blood samples were collected at baseline, 6 hours, and 1, 3 and 7 days post first immunization. Subtle changes in the transcriptomic profiles were observed following immunization, ranging from over 300 differentially expressed genes (DEGs) at day 1 to nearly 100 DEGs at day 7 following immunization. Functional pathway analysis revealed blood transcription modules (BTMs) related to general cell cycle activation, and innate immune cell activation at early time points, as well as BTMs related to T cells, and B cell activation at the later time points post immunization. Diverse CN54-gp140 specific serum antibody responses of the subjects enabled their categorization into high or low responders, at early (< 1 month) and late (up to 6 months) time points post vaccination. BTM analyses revealed repression of modules enriched in NK cells, and the mitochondrial electron chain, in individuals with high or sustained antigen-specific antibody responses. However, low responders showed an enhancement of BTMs associated with enrichment in myeloid cells and monocytes as well as integrin cell surface interactions. Flow cytometry analysis of peripheral blood mononuclear cells obtained from the subjects revealed an enhanced frequency of CD56dim NK cells in the majority of vaccinees 14 days after vaccination as compared with the baseline. These results emphasize the utility of a systems biology approach to enhance our understanding on the mechanisms of action of TLR4 adjuvanted human vaccines.